Geomagnetic storms: historical perspective to modern view - Lakhina, G.S.; Tsurutani, Bruce T. (My University, 2016)
The history of geomagnetism is more than 400 years old. Geomagnetic storms as we know them were discovered about 210 years ago. There has been keen interest in understanding Sun–Earth connection events, such as solar flares, CMEs, and concomitant magnetic storms in recent times. Magnetic storms are the most important component of space weather effects on Earth. We give an overview of the historical aspects of geomagnetic storms and the progress made during the past two centuries. Super magnetic storms can cause life-threatening power outages and satellite damage, communication failures and navigational problems. The data for such super magnetic storms that occurred in the last 50 years during the space era is sparce. Research on historical geomagnetic storms can help to create a database for intense and super magnetic storms. New knowledge of interplanetary and solar causes of magnetic storms gained from spaceage observations will be used to review the super magnetic storm of September 1–2, 1859. We discuss the occurrence probability of such super magnetic storms, and the maximum possible intensity for the effects of a perfect ICME: extreme super magnetic storm, extreme magnetospheric compression, and extreme magnetospheric electric fields.
Keywords: CME; Coronal mass ejection; Super magnetic storms; Space weather; Geomagnetic storms